Preparation of Curcumin-Loaded Liposomes and Evaluation of Their Skin Permeation and Pharmacodynamics - Lei Zhou; Xuan Liu; Ling Yuan; Zhenghai Zhang; Qingqing Wu; Yan Chen (Molecules, 2012)
This study aimed to investigate the in vitro skin permeation and in vivo antineoplastic effect of curcumin by using liposomes as the transdermal drug-delivery system. Soybean phospholipids (SPC), egg yolk phospholipids (EPC), and hydrogenated soybean phospholipids (HSPC) were selected for the preparation of different kinds of phospholipids composed of curcumin-loaded liposomes: C-SPC-L (curcumin-loaded SPC liposomes), C-EPC-L (curcumin-loaded EPC liposomes), and C-HSPC-L (curcumin-loaded HSPC liposomes). The physical properties of different lipsomes were investigated as follows: photon correlation spectroscopy revealed that the average particle sizes of the three types of curcumin-loaded liposomes were 82.37 ± 2.19 nm (C-SPC-L), 83.13 ± 4.89 nm (C-EPC-L), and 92.42 ± 4.56 nm (C-HSPC-L), respectively. The encapsulation efficiency values were found to be 82.32 ± 3.91%, 81.59 ± 2.38%, and 80.77 ± 4.12%, respectively. An in vitro skin penetration study indicated that C-SPC-L most significantly promoted drug permeation and deposition followed by C-EPC-L, C-HSPC-L, and curcumin solution. Moreover, C-SPC-L displayed the greatest ability of all loaded liposomes to inhibit the growth of B16BL6 melanoma cells. Therefore, the C-SPC-L were chosen for further pharmacodynamic evaluation. A significant effect on antimelanoma activity was observed with C-SPC-L, as compared to treatment with curcumin solution in vivo. These results suggest that C-SPC-L would be a promising transdermal carrier for curcumin in cancer treatment.